Ethics of consumption - Mashitoh Yaacob,; Zubaidah Mohd Nasir,; W. Syairah Hazwani W. Petra, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This article is based primarily on quantitative data from an actual study in discussing: (a) the consumption ethics of Muslims in Bandar Baru Bangi (BBB) Malaysia township, i.e., a recently crowned as ‘knowledge city’ and (b) the contextual aspects that encourage or discourage the Muslims to consume ethically. The ethical consumption behavior measured is categorized into two categories: (a) pre-cycling and (b) recycling & reusing, while the contextual aspect measured is categorized into four categories: (a) social; (b) religion; (c) economy and (d) politic. A quantitative methodology, i.e., survey questionnaire, was employed to tap information on the consumption ethics of Muslims in BBB as well as on the influence of the contextual aspects. Hence, the questionnaire was distributed to 563 Muslims in BBB, and 178 of them responded. Reliability and validity tests of 21 items, 5 scales each, were conducted using SPSS Version 19. Cronbach’s Alpha value obtained shows the reliability of the items are high (0.907) and Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy is 0.825. The test of validity shows rotated component matrix in two components which all items loaded above 0.30 and each item loaded with its proposed constructs. Frequency analysis was conducted to identify the frequency of ethical consumption behavior performed by respondents and the influence level of contextual aspects on the respondents’ ethical consumption behavior. For pre-cycling behavior the majority of respondents (50.6%) performed ‘sometimes’ and ‘rarely’ while for the reusing and recycling behavior 46.3% of the respondents performed ‘always’ and ‘most of the time’. Almost 60.0% of the respondents stated that contextual aspects have a ‘very strong’ and ‘strong’ influence on their ethical consumption behavior’s decision making. Pearson correlation demonstrates that the two categories of ethical consumption behavior have a positive correlation and statistically significant with all four categories of contextual aspects (either p < 0.01 or p<0.05).